Postoperative Illeus After Exploratory Laparotomy: Postoperative Illeus After Exploratory Laparotomy - Din, Bahr Ud; Nijat, Adil (Pakistan Journal of Health Sciences, 2026)
Postoperative ileus is a common and significant complication following abdominal surgery, particularly after exploratory laparotomy. It is characterized by a temporary impairment of gastrointestinal motility leading to delayed passage of bowel contents, abdominal distension, nausea, vomiting, and prolonged hospital stay. Identifying the frequency of postoperative ileus after exploratory laparotomy is essential for understanding its clinical burden and for improving perioperative management strategies aimed at reducing postoperative morbidity. Objectives: To determine the frequency of postoperative complications in patients undergoing emergency exploratory laparotomy for non-traumatic ileal perforation. Methods: This Analytical cross-sectional study was conducted from 15th July 2025 to 16th October 2025 at the Department of Surgery, Lady Reading Hospital, Peshawar. A total of 115 patients, aged 18–65 years, undergoing exploratory laparotomy were included using non-probability consecutive sampling. Results: The mean age was 41.08 ± 14.05 years, and 64.3% were male. Wound infection was the most frequent postoperative complication observed in 33 patients (28.7%), followed by peristomal excoriation in 19 (16.5%), postoperative ileus in 18 (15.7%), wound dehiscence in 13 (11.3%), and fistula formation in 3 patients (2.6%). Conclusions: Postoperative ileus remains a considerable complication after exploratory laparotomy. Diabetes, hypertension, obesity, and older age are important predictors.